Influence of idazoxan on analgesia, tolerance, and physical dependence of morphine in mice and rats in vivo - Su Rui-Bin; Li Jin; Gao Kai; Pei Gang; Qin Bo-Yi (Acta Pharmacologica Sinica; Vol 21, No 11 (November 2000): Acta Pharmacologica Sinica, 2016)
"AIM: To study the influence of idazoxan (Ida), an antagonist of imidazoline receptors (I-R), on analgesia, tolerance, and physical dependence of morphine. METHODS: The effects of Ida on pain threshold and morphine analgesia were observed in mouse acetic acid writhing test and 55 degrees C hot plate test. The effect of Ida on morphine tolerance and physical dependence were observed in mouse tolerant model and in mice and rat models. RESULTS: Ida (3-9 mg/kg) significantly decreased the pain threshold by 120% in acetic acid writhing test and by 39% in 55 degrees C hot plate test of mice, respectively. It inhibited the analgesic effect of morphine in a dose-dependent manner. Ida promoted the development of tolerance to morphine in mice and induced the abstinence syndrome in morphine-dependent mice and rats similar to naloxone. CONCLUSION: I-R and its endogenous ligand agmatine might participate in the pain threshold and influence morphine analgesia as well as negatively regulate tolerance to and physical dependence on morphine."